1972
DOI: 10.1007/bf00165268
|View full text |Cite
|
Sign up to set email alerts
|

A search for the solar Sr 87 content and the solar Rb/Sr ratio

Abstract: Some energy levels of Sr 87 shows hyperfine splitting which broadens strontium lines in the solar spectrum. By analysis of two faint photospheric Sr i lines of Multiplet No. 3 an upper limit of the relative Sr 87 content (Sr 87/Sr) of -} has been found. The terrestrial value is 0.07-0.075.The solar abundance of strontium found from the two lines is log esr = 2.90 in the log e~ = 12.00 scale. Using the solar rubidium abundance recently determined by the author (Hauge, 1972), one obtains e~b/esr = o.5 • This val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The line at 7070 A Ê though also very weak appears as a relatively clean line when the disc centre spectrum of Brault & Testermann (1972) is scaled up by a factor of 60. Hauge (1972) has shown that the theoretical log gf value for this line obtained by Gruzdev (1967) is midway between two empirical values, suggesting an uncertainty of^0X03. A section of spectrum containing this line is shown in Fig.…”
Section: Sr I Linesmentioning
confidence: 75%
“…The line at 7070 A Ê though also very weak appears as a relatively clean line when the disc centre spectrum of Brault & Testermann (1972) is scaled up by a factor of 60. Hauge (1972) has shown that the theoretical log gf value for this line obtained by Gruzdev (1967) is midway between two empirical values, suggesting an uncertainty of^0X03. A section of spectrum containing this line is shown in Fig.…”
Section: Sr I Linesmentioning
confidence: 75%
“…We treat each Sr line as a single component in our abundance calculations, as isotopic splitting is small for Sr lines (Hauge 1972b) …”
Section: Strontiummentioning
confidence: 99%
“…Some 7% of all the 87 Rb produced to that time would thus already have decayed to 87 Sr, accounting for some 10% of the solar inventory of 87 Sr. This contribution might have been lower if the mean age of 87 Rb were lower than that assumed, or higher if the ISM value of Rb/Sr were higher (e.g., Hauge 1972). In addition, approximately 6% of solar 86 Sr, but a substantially smaller fraction of 87 Sr, was contributed by the p-process rather than the s-process (Käppeler et al 1990).…”
Section: Discussionmentioning
confidence: 89%